Functional significance of vascular endothelial growth factor and its receptor (receptor-1) in various lung cancer types - Ilhan, N; Ilhan, N; Deveci, F (Pergamon-Elsevier Science Ltd, 2004)
Objectives: VEGF is one of the key factors in tumor angiogenesis that may be involved in tumor growth and metastasis. VEGF receptor, a naturally occurring soluble form of the VEGFR-1 (sVEGFR-1. flt-1), is produced by endothelial cells by differential splicing of the flt-1 gene, and is a negative counterpart of the VEGF signaling pathway. Design and Methods: We investigated the levels of VEGF and sVEGFR-1, a known intrinsic inhibitor of VEGF, in 42 patients with various types of lung cancers before beginning treatment and 18 healthy subjects. \ Results: Serum sVEGFR-1 levels (mean +/- SD, pg/ml) were 465.17 +/- 158.34 in patients and were significantly higher than those of the healthy subjects (156.39 +/- 89.17) (P < 0.0001). Serum VEGF levels of patients (449.48 +/- 175.54 pg/ml) were significantly higher in patients than in healthy subjects (77.06 +/- 47.26 pg/ml) (P < 0.0001). Conclusions: We conclude that increased sVEGFR-1 and VEGF levels are important parameters in lung cancers. (C) 2004 The Canadian Society of Clinical Chemists. All rights reserved.
Keywords: VEGF; sVEGFR-1; lung cancer